Difentano-70: Tratamiento electivo en Himenolepiasis nana - Jiménez-Quirós, Otto (1959)
1. After several years of testing various hymenolepicides with poor therapeutic results and frequent intolerances, Di phenthane-70, which has been reported effective against Taenia saginata, T. solium, and Dipylidium caninum, was tested in the treatment of 20 cases of Hymenclepis nana found among freshmen of the University of Costa Rica. 2. The treatment, aimed at the destruction of immature and mature in dividuals , consisted of daily doses of 3 gm of Diphenthane-70 given in three cycles of 5 days each with 10-day intervals, in order to eliminate the possibility of internal auto-infection which the action of the taenicide itself tends to favor. 3. Diphenthane-70 proved to have a cumulative toxic effect on the parasites and very slight toxicity for the patients in the doses employed. Intolerance phenomena were minimal, consisting mainly of soft feces, few and brief attacks of diarrhoea, colic pains, and in one doubtful instance, cutaneous allergic symptoms. 4. The convenience of Diphenthane-70 in out-patient treatment, and the Success obtained in 90 per cent, or better, of the cases, show this to be a highly recommendable drug for the treatment of hymenolepiasis nana, no cisticercoidicide being available at present.